Investigation of Chitosan, Quercetin and Water Interactions using Free Energy Calculations and Molecular Docking - Aguiar, Isabelle Caroline Alana da Silva; Stefani, Ricardo (Orbital: The Electronic Journal of Chemistry, 2019)
Predicting the preferred orientation of a ligand to a receptor and the free energy (ΔGAB) of these molecules in a solution is very useful for pharmaceutical applications. In this work, ΔGAB between chitosan and quercetin molecules with water were obtained by the thermodynamic integration (TI) method and the chitosan+quercetin complex was investigated by Molecular Docking (MDK). The topology of the molecules was compatible with the CHARMM force-field. Both molecules were solvated with the GROMACS SPC water model. The ΔGAB values of the molecule+water systems with the thermodynamic integration (TI) method was done in a 10 ns simulation. The complex was achieved in a 2.5 nm x 2.5 nm x 2.5 nm box. The ΔGAB values for the molecules+water systems were 14.36 +/- 0.46 and 0.19 +/- 0.53 kJ/mol, respectively. For the complex, nine conformations were obtained for the quercetin around the chitosan. The best conformation showed an affinity energy of -3.8 kcal/mol. The ΔGAB results for the systems confirm the low or no solubility of the molecules in the water under normal conditions, as already demonstrated experimentally. The docking showed that the interaction between chitosan and quercetin molecules involves hydrogen bonds in a specific position. DOI: http://dx.doi.org/10.17807/orbital.v11i2.1344